1 year weight losses in the Tianjin Gestational Diabetes Mellitus Prevention Program: a randomised trial. (November 2016) - Liu, Huikun; Wang, Leishen; Zhang, Shuang; Leng, Junhong; Li, Nan; Li, Weiqin; Tian, Huiguang; Qi, Lu; Tuomilehto, Jaakko; Yang, Xilin; Yu, Zhijie; Hu, Gang
Abstract: Background: Gestational diabetes affects about 8% of pregnant women in urban areas of China, and is an important indicator of risks of type 2 diabetes and impaired glucose tolerance later in life. The Tianjin Gestational Diabetes Mellitus Prevention Program aims to investigate the extent to which a postpartum lifestyle intervention given soon after delivery can reduce risk or delay onset of type 2 diabetes in women with gestational diabetes. Here, we report weight loss after the first year of the trial. Methods: The Tianjin Gestational Diabetes Mellitus Prevention Program is a randomised trial done at Tianjin Women's and Children's Health Center, Tianjin, China. We recruited women (aged >24 years) with gestational diabetes diagnosed on the basis of WHO criteria from six urban districts in Tianjin between July 1, 2005, and June 30, 2009. After participants completed the baseline survey administered by health workers from the study centre, eligible participants were randomly assigned (1:1) to receive a 4 year lifestyle intervention (intervention group) or standard care (control group). Statistical Package for the Social Science (SPSS) was used to generate a list of 1200 random allocation statuses, and the list of random assignments was kept centrally by an independent person. Major elements of the intervention included six face-to-face sessions with study dietitians and two telephone calls in the first year, and two individual sessions and two telephone calls in each subsequent year. Weight loss after the first year of the trial was analysed in patients with complete data. Ethics approval was granted by the human subjects committee of Tianjin Women's and Children's Health Center, and all participants provided written informed consent. This trial is registered withClinicalTrials.gov, numberNCT01554358, and is ongoing. Findings: Between Aug 1, 2009, and July 31, 2011, we recruited and randomly assigned 1180 women into the intervention group (n=586) or the control group (n=594). At the end of year 1, mean weight loss was 0·8 kg (SD 3·5; 1·1% [SD 5·4] of initial weight) in the intervention group and 0·1 kg (3·3; 0·03% [5·0%] of initial weight) in the control group (p<0·001). In prespecified subgroup analysis, weight loss was more pronounced in women who were overweight (BMI ≥24 kg/m 2 ) at baseline: mean weight loss was 2·0 kg (4·3; 2·9% [6·1%] of initial weight) in the intervention group and 0·44 kg (4·0; 0·5% [5·5%] of initial weight) in the control group (p<0·001). Compared with those in the control group, women in the intervention group had a greater decrease in body fat (0·50% vs 0·05% increase; p=0·001) and waist circumference (1·76 cm vs 0·73 cm; p=0·003). Interpretation: The 1 year lifestyle intervention led to significant weight loss after delivery in women who had gestational diabetes, and such an effect was more pronounced in those who were overweight. Our findings indicate that lifestyle intervention is feasible and effective in women with gestational diabetes. Funding: European Foundation for the Study of Diabetes–Chinese Diabetes Society–Lilly programme for Collaborative Research between China and Europe, Tianjin Women's and Children's Health Center, Tianjin Public Health Bureau, and the National Institute of Diabetes and Digestive and Kidney Diseases of the US National Institutes of Health (R01DK100790).